Pengaruh Overtime Kerja & Job Satisfaction Terhadap Work-Life Balance Karyawan di The Balcone Suites & Resort Bukittinggi - Putri Artha Pramesti; Hijriyantomi Suyuhtie (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
This study discusses how overtime & job satisfaction affect the work-life balance of employees at The Balcone Suites & Resort Bukittinggi. This research is in the background with the discovery of phenomena regarding overtime, job satisfaction, and work-life balance of employees of The Balcone Suites & Resort Bukittinggi. This type of research is quantitative descriptive with a sampling method using purposive sampling, involving 123 respondents. The research instrument in the form of a questionnaire was prepared using the Likert scale. The data obtained was then analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS) version 3.0. . The results of the hypothesis test show that Overtime Work has a negative and significant effect on Employee Work-Life Balance with a negative value of -0.474 and a tstatistic value of 4.224 > a Ttable value (1.96) with a p-value of 0.000 < 0.05. Job Satisfaction has a positive and significant effect on Employee Work-Life Balance with a value of 0.280 and a tstatistic value (2.745) > a ttable value (1.96) with a p-value of 0.006 < 0.05. Overtime Work and Job Satisfaction have an effect on Employee Work-Life Balance, with an R Square of 0.365 indicating that 36.5% of employee Work-Life Balance variables can be explained by the Overtime Work and Job Satisfaction variables and the remaining 63.5% are influenced by other variables that are not present in this study.